Wroxeter and the end of Roman Britain. (1st June 2014) - Lane, Alan
Abstract : When and how did urban life in Roman Britain end? The excavations conducted by Philip Barker at Wroxeter from 1966–1990 produced evidence suggesting a post-Roman phase of urban activity that continued into the sixth or seventh century AD, up to 200 years beyond the traditionally accepted chronology. Careful re-examination of the evidence, however, throws doubt on these claims. More recent work on Late Roman Britain coupled with new discoveries in Wales and the west challenges the evidence for the post-Roman survival of Wroxeter as an urban centre and suggests that it may have been largely abandoned, along with other Roman towns, in the late fourth or early fifth century AD.